2021
DOI: 10.1039/d0tc05934j
|View full text |Cite
|
Sign up to set email alerts
|

Doped crystalline thin-film deep-blue organic light-emitting diodes

Abstract: A doped crystalline thin-film deep-blue organic light-emitting diode (C-OLED) with high photon output and a low driving voltage is created through employing highly ordered and high-mobility organic semiconductor layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 31 publications
3
50
0
Order By: Relevance
“…The carriers can transport in the vertical direction with a hole mobility of 0.10 cm 2 V À1 s À1 and an electron mobility of 0.015 cm 2 V À1 s À1 , as measured in a previous study although the molecules adopt an edge-on arrangement on the substrate. 9 More importantly, the angle between the long axis and the substrate is 6.11 and the PPI moieties are perpendicular to the substrate. The electronic structures of 2FPPICz were calculated using density functional theory (DFT) in a previous study, 15 and the transition dipole moment was further calculated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The carriers can transport in the vertical direction with a hole mobility of 0.10 cm 2 V À1 s À1 and an electron mobility of 0.015 cm 2 V À1 s À1 , as measured in a previous study although the molecules adopt an edge-on arrangement on the substrate. 9 More importantly, the angle between the long axis and the substrate is 6.11 and the PPI moieties are perpendicular to the substrate. The electronic structures of 2FPPICz were calculated using density functional theory (DFT) in a previous study, 15 and the transition dipole moment was further calculated.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] However, high-performance OLEDs based on the crystalline route have not been widely realized even after many efforts. Recently, it was reported that efficient deep-blue luminescence has been achieved in crystalline OLEDs that consist of phenanthroimidazole derivatives, 8,9 which were fabricated via a facile physical vapor deposition technique, the weak epitaxy growth (WEG) method. 10,11 Phenanthroimidazole derivatives are a class of promising deep-blue light-emitting materials due to their advantages of having a wide-bandgap, bi-polar transport and high fluorescence quantum yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-OLEDs are capable of achieving much enhanced photoemission at the same driving voltage in OLEDs, owing to the high carrier mobility of crystalline thin films and the resultant rapid formation of excitons (24,40). Figure 5A shows the comparison of the brightness of the CHM-HENA-D OLED (2 wt % DSA-Ph) with reported typical blue OLEDs with high EQE, of which the CIE y coordinate values are close to but less than 0.20 (41)(42)(43).…”
Section: Photon Output Characteristicmentioning
confidence: 99%
“…There was no need to introduce HILs for the ITO-based devices since it has been shown in the literature that increased O 2 plasma durations (≈15 min) increase the work function of the ITO to desired levels. [55,56] It is also known that O 2 plasma treatment can modify the work function of Gr; however, longer plasma treatment durations result in unpredictable detachment of the graphene layers. Hence a short O 2 plasma treatment (≈5 min) to remove organic contaminants was performed on the Grcoated PET substrates before PEDOT:PSS deposition.…”
Section: Device Fabrication and Characterizationmentioning
confidence: 99%